Influence of Antitranspirant on Leaf Water Content and Transpiration of Sunflower* - EL-SHARKAWY, M. A.; ABOU-RAYA, M. A.; NAGI, MOHAMED (The Libyan Journal of Agriculture, 2023)
Leaf water saturation deficit (WSD) and relative turgidity (RT) of sunflower plants (Helianthus annuus L.), grown in Tripoli, were significantly affected by foliar spray of the antitranspirant ‘vapor gard'. Compared with the control, treatments with 2.5% and 5% ‘vapor gard' reduced WSD by 20% and 15%, whereas RT was increased by 6.5% and 5%, respectively. Highly significant correlation (r = —0.85) and regression coefficient (b = —0.98%) were found between WSD and RT as estimated by Stocker’s and Weatherley’sequations. • Transpiration rates of severed leaves were significantly reduced by treatments with ‘vapor gard'. Spraying with 2.5% ‘vapor gard’ reduced transpiration by 62% and 57% when the whole leaf and the upper surface were treated, respectively.